Technological Diversification of ICT companies into the Internet of things (IoT): A Patent -based Analysis - Bert Sadowski; Onder Nomaler; Jason Whalley (International Telecommunications Society (ITS), 2016)
The Internet-of-things (IoT) has been heralded as the third industrial revolution combining disruptive technological change and a radical restructuring of the traditional ICT ecosystem. Technological diversification allows companies in the information and communication technology (ICT) industries to participate in the IoT by transplanting their existing know-how to new application domains. In using the ICT ecosystem perspective, this paper examines the diversification of 1323 ICT companies into IoT by investigating 86,159 main patents in the IoT area using the USPTO database. The paper examines the extent to which the existing knowledge base allows ICT firms to diversify into the new technological area, that is, IOT. It utilizes an entropy measure to characterize the extent to which ICT firms diversify into IoT. We propose that a firm's knowledge position in a new emerging technological has an important strategic value in terms of competitiveness. It characterizes a few new application domains in neighboring industries like health or transport. The paper concludes that due to technological pervasiveness Iot provides for new innovative activities and technological opportunities for ICT companies to grow in emerging sectors like wearables, industrial automation, smart energy and smart mobility.
Keywords: 330